2015
DOI: 10.1063/1.4938243
|View full text |Cite
|
Sign up to set email alerts
|

Band structure of topological insulators from noise measurements in tunnel junctions

Abstract: The unique properties of spin-polarized surface or edge states in topological insulators (TIs) make these quantum coherent systems interesting from the point of view of both fundamental physics and their implementation in low power spintronic devices. Here we present such a study in TIs, through tunneling and noise spectroscopy utilizing TI/Al 2 O 3 /Co tunnel junctions with bottom TI electrodes of either Bi 2 Te 3 or Bi 2 Se 3 . We demonstrate that features related to the band structure of the TI materials sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…However, sensitivity of these surface states to different types of disorder is still a matter of active debate [4][5][6][7][8][9][10]. Recently, flicker noise or 1/f -noise in bulk TI systems has been established as a powerful tool not only as a performance-marker for electronic applications but also for defect-spectroscopy and even band structure determination [8,11,12]. Noise measurements in exfoliated TI devices from bulk crystals have revealed that in the thickness range of 50 nm to 80 µm charge number fluctuations in the bulk can give rise to the resistance fluctuations in the surface states [8].…”
mentioning
confidence: 99%
“…However, sensitivity of these surface states to different types of disorder is still a matter of active debate [4][5][6][7][8][9][10]. Recently, flicker noise or 1/f -noise in bulk TI systems has been established as a powerful tool not only as a performance-marker for electronic applications but also for defect-spectroscopy and even band structure determination [8,11,12]. Noise measurements in exfoliated TI devices from bulk crystals have revealed that in the thickness range of 50 nm to 80 µm charge number fluctuations in the bulk can give rise to the resistance fluctuations in the surface states [8].…”
mentioning
confidence: 99%
“…In addition to the ratio of the MR and its anisotropy, another key factor that determines the device performance (accuracy and sensitivity) is the level of low‐frequency flicker noise (or the 1/ f noise) present in the device. 1/ f noise has been explored in TI systems . TRS protection can lead to noise reduction in TI surfaces.…”
Section: Low 1/f Noise In Topological Insulatorsmentioning
confidence: 99%
“…Conventional transport measurements cannot provide a clear signature of the crystal defects and impurity bands. 1/ f noise has been used to demonstrate the band structure of the TI electrodes in perpendicular tunneling junctions through an Al 2 O 3 barrier, which could pave the way for the manipulation of their spin‐polarized currents for technological purposes . 1/ f noise has also been explored in magnetically doped Cr x (Bi,Sb) 2‐ x Te 3 to estimate whether the samples are highly disordered …”
Section: Low 1/f Noise In Topological Insulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is remarkable that while the insulating bulk of the TI does not directly contribute to electrical conduction, it appears to be the dominant source of 1/f noise in TI-based devices. The effect of bandstructure of TIs has also been investigated by measuring 1/f spectra [126] in perpendicular tunnel junctions. In Figure 5(e), the device geometry consisting of a bottom electrode of MBE grown Bi 2 Se 3 /Bi 2 Te 3 and Co with Al 2 O 3 as a tunnel barrier is shown.…”
Section: Bismuth Chalcogenidesmentioning
confidence: 99%